THE EFFECT OF EGRANG TRADITIONAL GAME TOWARD THE IMPROVEMENT OF PHYSICAL ACTIVITIES FOR THE 10-12 YEAR CHILDREN - Dhanang Puspita; Rosiana Eva Rayanti; Galih Wibisono (Universitas Negeri Medan, 2019)
The current problem was that children are lazy to move / sedentary due to technological development and the direct impact was decreased ability, delay in development and growth of children. One of the recommended physical activities was with stilts as a traditional Game. The purpose of this study was to determine the effect of engrang traditional games on increasing physical activity of children aged 10-12 years. This research was quantitative descriptive with a population of 40 children, aged 10-12 years, male sex. The parameters measured are; strength, balance, coordination, endurance, and agility. The results showed a significant increase in physical activity for coordination, while strength, endurance, and balance were not so significant and agility actually decreased. It was concluded that play engrang could improve children's coordination.